Landscapes of hope anti-colonial utopianism in America - Ahmad, Dohra (Oxford : Oxford University Press, 2009)
This volume examines anti-colonial discourse during the understudied but critical period before World War Two, with a specific focus on writers and activists based in the United States.
Description based on print version record.
Includes bibliographical references and index.
Keywords: American literature -- History and criticism; Utopias in literature; Anti-imperialist movements -- United States; Authors, American -- Political and social views; Race in literature; Nationalism in literature